Potentially paraneoplastic glomerulopathies in a Brazilian cohort: a retrospective analysis - Marcella Soares Laferreira; Gianna Mastroianni Kirsztajn (Brazilian Journal of Nephrology)
Abstract Introduction: Glomerular diseases can be associated with solid or hematopoietic malignancies. The prevalence of these associations varies according to the studied glomerular disease. This study aimed to evaluate the frequency and type of neoplasms in patients with glomerular diseases as well as their clinical, laboratory, and histopathological features and the relationship with immunosuppressive therapy. Methods: This was a retrospective, descriptive, observational, longitudinal study that reviewed 4,820 medical records and included 95 patients with glomerular disease and neoplasms. Demographic, clinical, laboratory, and histologic data were collected. Results: The prevalence of neoplasms was 1.97% (95 patients; 81 [85.3%] malignant, 14 [14.7%] benign). Hematologic malignancies (35.8%) showed the highest prevalence, followed by colon, rectal, and gynecologic tumors. The glomerulopathy with the highest frequency was membranous glomerulopathy (MGN, 25 patients, 35.7%). The dose of the immunosuppressive agents among patients with neoplasms before or after immunosuppression was not statistically different. Neoplasm was diagnosed before glomerulopathy in 53% of patients. Among cases in which neoplasms were diagnosed after glomerulopathy, 43% were diagnosed in the first year of follow-up of the renal disease. The predominant syndrome at presentation was nephrotic syndrome. Progression to chronic kidney disease stage 5 at the end of follow-up occurred in 8.4% of the cases. Conclusions: Neoplasms manifested before or, less frequently, after the diagnosis of glomerular diseases. As neoplasms diagnosed after presentation of glomerulopathy often appeared early after this diagnosis, it is necessary to be aware of neoplasms during the first year of follow-up of glomerulopathies, especially in patients with nephrotic syndrome, and MGN.